2022
DOI: 10.1371/journal.pone.0265896
|View full text |Cite
|
Sign up to set email alerts
|

Odorant Binding Proteins (OBPs) and Odorant Receptors (ORs) of Anopheles stephensi: Identification and comparative insights

Abstract: Anopheles stephensi is an important vector of malaria in the South Asia, the Middle East, and Eastern Africa. The olfactory system of An. stephensi plays an important role in host-seeking, oviposition, and feeding. Odorant binding proteins (OBPs) are globular proteins that play a pivotal role in insect olfaction by transporting semiochemicals through the sensillum lymph to odorant receptors (ORs). Custom motifs designed from annotated OBPs of Aedes aegypti, Drosophila melanogaster, and Anopheles gambiae were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Insects rely on their sensitive olfactory system to detect plant volatiles and pheromones ( Hansson and Stensmyr, 2011 ; Deisig et al, 2012 ), but the specific molecular mechanisms of olfaction in X. affinis for locating hosts have not been fully understood. Identifying the proteins responsible for olfactory perception is crucial to further comprehending the molecular mechanisms of the olfactory system ( Clark and Ray, 2016 ; Zafar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insects rely on their sensitive olfactory system to detect plant volatiles and pheromones ( Hansson and Stensmyr, 2011 ; Deisig et al, 2012 ), but the specific molecular mechanisms of olfaction in X. affinis for locating hosts have not been fully understood. Identifying the proteins responsible for olfactory perception is crucial to further comprehending the molecular mechanisms of the olfactory system ( Clark and Ray, 2016 ; Zafar et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that these proteins are evolutionarily conserved and may have similar biological functions. Classic OBPs, characterized by six cysteine residues, form three disulfide bonds that are crucial in creating the binding pocket and stabilizing the three-dimensional structure ( Zhang et al, 2011 ; Pelosi et al, 2014 ; Zafar et al, 2022 ). Previous studies suggested that the loss of one disulfide bridge in minus-C OBPs might have functional relevance, as it could generate a more flexible structure ( Vieira and Rozas, 2011 ; Li et al, 2015 ; Zheng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling approaches are suited to reach this goal. They allow us to discover original structural scaffolds with a repellent activity and also better understand the mechanisms of action of new and existing repellents [15,55,56].…”
Section: Discussionmentioning
confidence: 99%